2013
DOI: 10.1016/j.seizure.2013.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Seizures after cerebrovascular events: Risk factors and clinical features

Abstract: In conclusion, our data show that epileptic seizures occur in particular after major strokes and in sinus thrombosis. Interestingly, conventional vascular risk factors were not associated with the occurrence of post-stroke seizures. Considering the risk for seizures after certain types of cerebrovascular events might help to early identify patients for anticonvulsive treatment. In the future, it should be investigated whether these patients might benefit from pre-emptive anticonvulsant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
84
2
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 43 publications
13
84
2
17
Order By: Relevance
“…We prescribed phenytoin as the first line of AED in acute Neuro ICU setting for patients of stroke with early onset seizure because of the ease of parenteral administration and cost effectiveness, even though more than 50% had partial seizures in one or other form and oxcarbamazepine as an additional drug. Julian et al [17] found that NIHSS score was significantly higher in patients with seizures (7.7 ± 6.1), than in patients without seizures (4.3 ± 4.9). In our study we didn't find any statistical significance in NIHSS score in stroke patients with or without early onset seizures.…”
Section: Discussionmentioning
confidence: 97%
“…We prescribed phenytoin as the first line of AED in acute Neuro ICU setting for patients of stroke with early onset seizure because of the ease of parenteral administration and cost effectiveness, even though more than 50% had partial seizures in one or other form and oxcarbamazepine as an additional drug. Julian et al [17] found that NIHSS score was significantly higher in patients with seizures (7.7 ± 6.1), than in patients without seizures (4.3 ± 4.9). In our study we didn't find any statistical significance in NIHSS score in stroke patients with or without early onset seizures.…”
Section: Discussionmentioning
confidence: 97%
“…Conrad ve ark. [7] 593 hastadan oluşan bir araştırmada çok ciddi inme ve sinüs trombozuna sahip kişilerde epilepsi nöbeti prevalansı %11.6 saptanmıştır. Lezyon lokalizasyonu ise nöbet riskini etkilememişti.…”
Section: Discussionunclassified
“…[7] Ayrıca serebrovasküler hastalığa yol açan konvansiyonel risk faktörlerinin poststrok epilepsi riskiyle ilişkili olmadığı bulunmuştu. [7] Yaptığımız çalışmada ise etkilenen damar alanları incelendi; en fazla medial serebral arter (MCA), ikinci sırada anterior serebral arter (ACA) gelmekteydi. Posterior serebral arter (PCA) alanına ait inme olgusu yoktu.…”
Section: Discussionunclassified
“…Demansta epilepsi insidansı çok değişken oranlarda (%5-64) bildirilmiştir (21). Non-vasküler demans ve Alzheimer hastalığı ilerlediğinde epileptik nöbet geçirme insidansı artmaktadır.…”
Section: Discussionunclassified